Resin-based aluminum oxide reinforced zirconium oxide composite slurry as well as preparation method and application thereof

By introducing resin-based alumina enhancer into zirconia ceramics, optimizing process parameters, and preparing composite slurries with suitable flowability and mechanical properties, the agglomeration phenomenon and crown stress concentration problems in the additive manufacturing of traditional zirconia ceramics are solved, and efficient preparation and performance improvement of dental restoration materials are achieved.

CN119823563APending Publication Date: 2025-04-15HUAQIAO UNIVERSITY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510019756.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

In the additive manufacturing process of traditional zirconia ceramics, the agglomeration of ceramic powders leads to poor fluidity, affecting the printing and forming accuracy, and the strength and hardness of the whole-ceramic crown is too high and the toughness is insufficient, which makes it easy to cause stress concentration and porcelain collapse during occlusal.

Method used

Resin-based alumina-enhanced zirconia composite slurry is used to optimize the formulation and process parameters, including the ratio and mixing process of photocuring resin, ceramic powder, photoinitiator, dispersant and organic additives, and the materials obtained by photocuring 3D printing technology are prepared.

Benefits of technology

The mechanical properties of the material are improved, including compressive strength, flexural strength, elastic modulus and Vickers hardness, making it more improved compared with natural teeth and are suitable for dental restoration, especially the preparation of dental crowns.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119823563A_ABST
    Figure CN119823563A_ABST
Patent Text Reader

Abstract

The invention discloses resin-based aluminum oxide reinforced zirconium oxide composite slurry as well as a preparation method and application thereof. The resin-based aluminum oxide reinforced zirconium oxide composite slurry comprises light-cured resin, ceramic powder, a photoinitiator, a dispersing agent and an organic auxiliary agent, wherein the light-cured resin is prepared from urethane acrylate, polyester acrylate, titanium dioxide and silicon dioxide according to the mass ratio of (20 to 55) to (15 to 35) to (0.2 to 2) to (1 to 8); the ceramic powder comprises zirconium oxide and aluminum oxide in a mass ratio of 4: 1; the mass ratio of the photoinitiator to the light-cured resin is 1: 100, the mass ratio of the dispersing agent to the organic additive to the ceramic powder is 1: 3: 100, and the mass ratio of the ceramic powder to the light-cured resin is 15: 85. Various mechanical properties of the resin-based alumina reinforced zirconia composite material prepared through printing are moderate and are improved compared with those of natural teeth, and the resin-based alumina reinforced zirconia composite material is suitable for dental restoration.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of tooth restoration, and in particular relates to a resin-based alumina reinforced zirconia composite slurry and a preparation method and application thereof. Background Art

[0002] According to the "Fourth National Oral Health Epidemiological Survey Report" (2018), the average number of missing teeth for adults over 35 years old in my country is 4.7, and the cumulative number of missing and damaged teeth in different age groups reaches billions. Damage and loss of teeth not only affect people's normal chewing function, but also affect their appearance. Therefore, the demand for oral treatment related to tooth restoration is growing. With the improvement of material living standards, consumers have shifted more attention to physical and mental health, and the demand for oral medical services has also shifted from health maintenance and disease treatment to beauty and restoration. From the initial use of allogeneic teeth and animal teeth for simple replacement, to the modern advancement of science and technology and the development of materials science, human dental restoration materials have gone through three main stages: metal, polymer and ceramic materials. Among them, zirconia all-ceramic materials are favored because of their good safety, long durability, and aesthetic properties similar to those of natural teeth, and have become the current mainstream dental restoration material.

[0003] However, the traditional subtractive manufacturing process has serious material waste, and the processing of complex structures such as tiny curved surfaces is limited, making it difficult to efficiently produce high-quality products. The flexibility and freedom of additive manufacturing technology can not only achieve efficient and rapid preparation of zirconia ceramics for dental restorations, but also meet the precise, complex and personalized needs of the dental field. The main process flow of the existing additive manufacturing to obtain zirconia ceramics is: adding a small amount of resin as a binder to the zirconia ceramic powder for printing, and then obtaining zirconia ceramics through degreasing and sintering. There are still the following problems: the slurry with ceramic powder added is prone to agglomeration, and improper handling will lead to poor fluidity, affecting the printing and molding accuracy and the inability of the ceramic powder to exert a good reinforcement effect; in addition, the crown prepared with all-ceramic is too high in strength and hardness and insufficient toughness, which is prone to stress concentration and porcelain collapse during occlusion. Summary of the invention

[0004] The purpose of the present invention is to provide a resin-based alumina reinforced zirconia composite slurry and a preparation method and application thereof, wherein the resin-based alumina reinforced zirconia composite slurry has suitable viscosity and flow properties, and the various mechanical properties of the printed resin-based alumina reinforced zirconia composite material are moderate and improved compared with natural teeth, and are suitable for dental restoration.

[0005] The technical solution of the present invention is as follows:

[0006] A resin-based alumina reinforced zirconia composite slurry, comprising a light-curing resin, a ceramic powder, a photoinitiator, a dispersant and an organic additive;

[0007] The photocurable resin includes polyurethane acrylate, polyester acrylate, titanium dioxide and silicon dioxide in a mass ratio of 20-55:15-35:0.2-2:1-8;

[0008] The ceramic powder includes zirconium oxide and aluminum oxide in a mass ratio of 4:1;

[0009] The mass ratio of the photoinitiator to the photocurable resin is 1:100, the mass ratio of the dispersant, the organic additive and the ceramic powder is 1:3:100, and the mass ratio of the ceramic powder to the photocurable resin is 15:85.

[0010] In some preferred implementations, the organic adjuvant is tributyl citrate (tributylcitrate).

[0011] In some preferred implementations, the polyester acrylate is ethylene glycol dimethacrylate.

[0012] In some preferred implementations, the photoinitiator is diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide.

[0013] In some preferred implementations, the average particle size of zirconium oxide is 200-300 nm.

[0014] In some preferred implementations, the aluminum oxide is in the form of spherical particles with a diameter of 1-2 μm.

[0015] A method for preparing the above-mentioned resin-based alumina reinforced zirconia composite slurry comprises the following steps:

[0016] Mix the photocurable resin, photoinitiator, dispersant and organic additive and stir for 30 minutes. Then add the ceramic powder, mix well and defoam.

[0017] In some preferred implementations, the mixing operation is to place the mixture in a ball mill and perform ball milling for 1 hour.

[0018] In some preferred implementations, the defoaming method is ultrasonic defoaming.

[0019] A resin-based alumina reinforced zirconia composite material is obtained by light curing the resin-based alumina reinforced zirconia composite slurry.

[0020] In some preferred implementations, the photocuring process is photocuring 3D printing, and the exposure power of photocuring 3D printing is 12-18 MW / cm 2 , exposure time was 3-5s, and slice thickness was 25, 50, or 75μm.

[0021] In some preferred implementations, the exposure power of the light-curing 3D printing is 18 MW / cm2 , exposure time was 5 s, and slice thickness was 50 μm.

[0022] Application of the above resin-based alumina reinforced zirconia composite slurry in the preparation of tooth restoration materials.

[0023] Application of the above resin-based alumina reinforced zirconia composite material in the preparation of artificial dental crowns.

[0024] The present invention has at least the following beneficial effects:

[0025] The present invention provides a resin-based alumina reinforced zirconia composite slurry and a preparation method and application thereof, wherein the resin-based alumina reinforced zirconia composite slurry has suitable flow properties and stability, and the various mechanical properties of the resin-based alumina reinforced zirconia composite material printed by the slurry are moderate and improved compared with natural teeth, and the slurry is suitable for dental restoration. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 is a viscosity curve diagram of the slurry of each experimental group in Example 1;

[0027] Figure 2 is a viscosity curve diagram of the slurry of each experimental group in Example 2;

[0028] Figure 3 Schematic diagram of the standard specimen used for the flexural strength and elastic modulus tests in Examples 2 and 3;

[0029] Figure 4 Schematic diagram of the standard specimen used for compressive strength and Vickers hardness tests in Examples 2 and 3;

[0030] Figure 5 is a curve chart of the compressive strength test of the standard samples prepared in each experimental group in Example 2;

[0031] Figure 6 is a schematic diagram of the compressive strength of each experimental group calculated in Example 2;

[0032] Figure 7 is a curve chart of the bending strength test of the standard specimens prepared in each experimental group in Example 2;

[0033] Figure 8 is a schematic diagram of the flexural strength of each experimental group calculated in Example 2;

[0034] Fig. 9 is a schematic diagram of the elastic modulus of each experimental group calculated in Example 2;

[0035] Fig.10 is a schematic diagram of the Vickers hardness of each experimental group calculated in Example 2;

[0036] Fig.11 This is a sedimentation curve diagram of the slurry of the experimental group with Z:A=4:1 in Example 2;

[0037] Fig.12 This is a photo of the artificial crown printed according to the optimized process parameters in Example 3. DETAILED DESCRIPTION

[0038] The technical solution of the present invention is further illustrated and described below through specific implementation methods.

[0039] In the following examples, the water used can be one or more of distilled water, purified water, and drinking water; unless otherwise specified, the detection methods in the following examples are conventional detection methods; the reagents in the following examples are purchased from commercial channels unless otherwise specified.

[0040] In the following examples, the organic additive is tributyl citrate (tributyl citric acid), with the molecular formula C 18 H 32 O7 (molecular weight 360.443); polyurethane acrylate molecular formula is C 11 H9F3O3 (molecular weight 246.183); polyester acrylate molecular formula is C 10 H 14 O4 (molecular weight 198.216); the photoinitiator is TPO, the average particle size of zirconium oxide is 200-300nm, and the aluminum oxide is spherical particles with a diameter of 1-2μm.

[0041] In the following examples, the compressive strength, flexural strength, elastic modulus and Vickers hardness were tested according to GB / T 8489-2006, GB / T 6569-2006, GB / T 10700-2006 and GB / T16534-2009 standards.

[0042] In the following examples, solid content refers to the proportion of the mass of the ceramic powder in the total mass of the ceramic powder and the photocurable resin.

[0043] Example 1 Optimization of the amount of ceramic powder added

[0044] In this group of experiments, the solid contents of the 7 experimental groups were designed to be 0wt.%, 5wt.%, 10wt.%, 15wt.%, 20wt.%, 25wt.% and 30wt.%, respectively.

[0045] The photocurable resin comprises polyurethane acrylate, polyester acrylate, titanium dioxide and silicon dioxide in a mass ratio of 55:35:2:8. The mass ratio of the photoinitiator to the photocurable resin is 1:100.

[0046] The mass ratio of the dispersant, the organic additive and the ceramic powder is 1:3:100, and the mass ratio of the organic additive and the ceramic powder is 3:100. The mass ratio of zirconium oxide and aluminum oxide in the ceramic powder is 1:0 (that is, all zirconium oxide).

[0047] The preparation method of the experimental group includes the following steps:

[0048] (1) A photocurable resin, a photoinitiator, an organic additive and a dispersant are placed in a container, stirred for 30 minutes using a magnetic stirrer to obtain a resin system, and the mixture is kept away from light for later use.

[0049] (2) adding ceramic powder to the resin system according to the solid content of each group, mixing, and putting into a ball mill for 1 hour to make it fully and evenly mixed, and then removing bubbles in the slurry by ultrasonic wave to obtain a resin-based alumina reinforced zirconia composite slurry.

[0050] The viscosity of the resin-based alumina reinforced zirconia composite slurry was tested, and the results were as follows: Figure 1 When the solid content is 15wt.%, the viscosity of the resin-based alumina reinforced zirconia composite slurry is 810MPa·s. At this time, the rheological properties of the slurry are more suitable as a printing slurry, so the solid content of the resin-based alumina reinforced zirconia composite slurry is determined to be 15wt.%.

[0051] Example 2 Optimization of ceramic powder components

[0052] In this embodiment, the solid content is determined to be 15wt.% according to the test results of Example 1. The mass ratio (Z:A) of zirconium oxide (Z) and aluminum oxide (A) in each experimental group is designed to be 8:1, 6:1, 4:1, 2:1, and 1:1. The blank group does not add ceramic powder (rd110), and the ceramic powder of the control group is zirconium oxide (15% Z). The remaining components and preparation method are the same as those in Example 1. Figure 2 As shown, the viscosity of each experimental group is in the range of 807-820 MPa·s, which is suitable for use as slurry for 3D printing.

[0053] The slurries of the experimental group, blank group and control group were printed with AUTOCERA-R digital light processing printer (Beijing Shiwei Technology Co., Ltd.) to print the test models, and the main printing parameters were set to an exposure power of 15 MW / cm 2 , the exposure time is 3s, the slice thickness is 50μm, and the following is obtained: Figure 3 and Figure 4 Standard specimen shown.

[0054] The compressive strength, flexural strength, elastic modulus and Vickers hardness of the standard specimens prepared in each experimental group were tested. The results are as follows Figure 5-Figure 10As shown. It can be seen that when Z:A=4:1, its compressive strength is the best, and it has higher flexural strength, elastic modulus and Vickers hardness. Therefore, the mass ratio of zirconium oxide to alumina in the resin-based alumina reinforced zirconium oxide composite slurry is determined to be 4:1. The viscosity of the slurry obtained by this mass ratio is 813MPa·s, and the sedimentation is good, as shown in FIG. Fig.11 As shown, the sedimentation rate was less than 5% within 8 hours.

[0055] Example 3 Optimization of printing parameters

[0056] In this embodiment, based on the test results of Embodiment 1 and Embodiment 2, the solid content is determined to be 15 wt.%, and the mass ratio of zirconium oxide to aluminum oxide is determined to be 4:1.

[0057] The printing parameters were optimized through orthogonal experiments. The factor levels are shown in Table 1, and the test performance of each group is shown in Table 2. It can be seen that each group can achieve better compressive strength, bending strength and Vickers hardness. Further, the optimal molding process parameters were fitted according to the orthogonal experimental results, and the optimal molding process parameter combination was obtained as an exposure power of 18MW / cm 2 , exposure time is 5s, slice thickness is 50μm, the Vickers hardness, compressive strength, flexural strength and elastic modulus under the optimal molding process parameters are 396.35HV, 334.24MPa, 106.93MPa and 87.49GPa respectively, which are improved compared with the mechanical properties of natural teeth. According to the optimal molding process parameter combination, artificial crowns are printed, and products such as Fig.12 shown.

[0058] Table 1 Orthogonal test factor level table

[0059]

[0060] *After calculation, the P values ​​of A, B, and C are all ≤0.01.

[0061] Table 2 Orthogonal test sample performance table

[0062]

[0063] The above are only preferred embodiments of the present invention, and the scope of implementation of the present invention cannot be limited thereto. Equivalent changes and modifications made according to the patent scope of the present invention and the contents of the specification should still fall within the scope of the present invention.

Claims

1. A resin-based alumina reinforced zirconia composite slurry, characterized in that: Including photocurable resin, ceramic powder, photoinitiator, dispersant and organic additive; Wherein, the photocurable resin comprises polyurethane acrylate, polyester acrylate, titanium dioxide and silicon dioxide in a mass ratio of 20-55:15-35:0.2-2:1-8; The ceramic powder comprises zirconium oxide and aluminum oxide in a mass ratio of 4:1; The mass ratio of the photoinitiator to the photocurable resin is 1:100, the mass ratio of the dispersant, the organic additive and the ceramic powder is 1:3:100, and the mass ratio of the ceramic powder to the photocurable resin is 15:

85.

2. The resin-based alumina reinforced zirconia composite slurry according to claim 1, characterized in that: The organic auxiliary agent is tributyl citrate (tributyl citric acid); The polyester acrylate is ethylene glycol dimethacrylate; The photoinitiator is diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide.

3. The resin-based alumina reinforced zirconia composite slurry according to claim 1, characterized in that: The average particle size of the zirconium oxide is 200-300 nm; The aluminum oxide is in the form of spherical particles with a diameter of 1-2 μm.

4. A method for preparing the resin-based alumina reinforced zirconia composite slurry according to any one of claims 1 to 3, characterized in that: The steps include: Mix the photocurable resin, photoinitiator, dispersant and organic additive and stir for 30 minutes. Then add the ceramic powder, mix well and defoam.

5. The preparation method according to claim 4, characterized in that: The mixing operation is to put the mixture into a ball mill and grind it for 1 hour; The defoaming method is ultrasonic defoaming.

6. A resin-based alumina reinforced zirconia composite material, characterized in that: The resin-based alumina reinforced zirconia composite slurry as described in any one of claims 1 to 3 is obtained by photocuring.

7. The resin-based alumina reinforced zirconia composite material according to claim 6, characterized in that: The photocuring process is photocuring 3D printing, and the exposure power of the photocuring 3D printing is 12-18MW / cm 2 , exposure time was 3, 4, or 5 s, and section thickness was 25, 50, or 75 μm.

8. The resin-based alumina reinforced zirconia composite material according to claim 7, characterized in that: The exposure power is 18 MW / cm 2 , the exposure time is 5 s and the slice thickness is 50 μm.

9. Use of the resin-based alumina reinforced zirconia composite slurry according to any one of claims 1 to 3 in the preparation of tooth restoration materials.

10. Use of the resin-based alumina reinforced zirconia composite material according to any one of claims 6 to 8 in the preparation of artificial dental crowns.

Citation Information

Patent Citations

  • Dental zirconia ceramic restoration

    CN105924158A

  • Method for preparing dental zirconia prosthesis based on stereo-lithography rapid prototyping technology

    CN109574657A

  • Method for preparing ZTA ceramic device by DLP (Digital Light Processing) 3D printing technology

    CN110511002A

  • Cigarette case with built-in cigarette butt storage

    KR102653260B1